(untitled) (UNIZIK Journal of Marketing, 2026)
The study investigated the effect of marketing intelligence on customer satisfaction among deposit money banks in Enugu state Nigeria. The study centered on how marketing intelligence variables including product intelligence, competitor intelligence, customer intelligence and market intelligence affect customer satisfaction. A cross sectional survey research design was adopted using customers of deposit money banks in Enugu state as the population. The population size was unknown while the sample size was 384. Primary source of data was used while the instrument of data collection was a structured questionnaire. The validity of the instrument was tested using expert opinion while the reliability of the research instrument was tested using Cronbach Alpha coefficient. The study used a purposive sampling technique in reaching the respondents. Multiple regression statistical analysis method was used for inferential statistical analysis while descriptive analysis was carried out using tables, frequencies and percentages. The study revealed that product intelligence, competitor intelligence, customer intelligence and market intelligence have significant and positive effect on customer satisfaction. It was concluded that the marketing intelligence dimensions understudy have significant and positive effect on customer satisfaction. The study recommended that deposit money banks should ensure improved usage of the studied marketing intelligence dimensions for enhanced customer satisfaction with their service offerings in Enugu state.